Natural transmission of Plasmodium knowlesi to humans by Anopheles latens in Sarawak, Malaysia - Vythilingam, I.; Tan, C.H.; Asmad, M.; Chan, S.T.; Lee, K.S.; Balbir, Singh (Elsevier Ltd., 2006)
Four species of malaria parasites are known to infect humans. A fifth species, Plasmodium knowlesi, has been reported to infect humans in Malaysian Borneo. Here we report for the first time the incrimination of Anopheles latens as the vector of P. knowlesi among humans and monkeys in Sarawak, Malaysia.